دور الفيسبوك في النشاط الجمعوي الخيري - التجاني وفاء; تربح خلود نور الهدى (جامعة عمار ثليجي الاغواط, 2024)
: تناولت هذه الدراسة بعد البحث والمناقشة موضوع –دور الفيسبوك في النشاط الجمعوي الخيري- دراسة حالة لجمعية البركة عبر -صفحة الفيسبوك- لما له من أهمية كبيرة في تفعيل خدمة الجمعيات الخيرية، الا أنه تناقش من زوايا مختلفة و حيث تم التطرق إلى أهم العناصرَ المشتركة بينهما والاستفادة من الخصائص التي تمنحها الجمعية. وانطلقت الدراسة من الاشكالية التالية : -كيف يساهم –الفيسبوك-في تفعيل النشاط الجمعوي الخيري ؟ وللاجابة عنها قسمت الدراسة الى جانبين :الجانب النظري والجانب التطبيقي، وتضمن الجانب النظري فصلين الفصل الأول المعنون تحت مدخل الى مواقع التواصل الاجتماعي، والفصل الثاني تحت عنوان النشاط الجمعوي الخيري .أما الجانب التطبيقي قد تضمن ثلاث مباحث : المبحث الأول تقديم شامل للجمعية ،المبحث الثاني عينة الدراسة ، المبحث الثالث تحليل النتائج ومناقشتها وفق فرضيات . وبعد جمع المادة ومناقشتها من أطراف متعددة توصلنا الى النتائج التالية : تكمن أهمية الفيسبوك في كون أن الحملات الخيرية عبرها فعالة. يقترن دورالفيسبوك في نجاح نشاطات وبرامج الجمعية بالترويج للأنشطة الخيرية. لا يمكن للجمعية الاستغناء عن الفيسبوك حيث تحرص الجمعية على تسجيل حضورها الدائم. الكلمات المفتاحية: الفيسبوك، الجمعيات الخيرية ،جمعية البركة الخيرية، الأغواط. Study summary : This study, after research and discussion, dealt with the topic of Al Baraka Society via the facebook page, because it has a great importance in activating the service of charities, it discussed from different angles, where the most important elements shared the role of social media sites in charitable activity, a case study between them and the utilization of the characteristics given by the association. The study began with the following problems: - How do - Facebook - contribute to activating charitable activity? In response, the study was divided into both theoretical and applied aspects. The theoretical aspect included two chapters, chapter I, entitled "portal", and chapter II, entitled "Philanthropic activity". The applied aspect included three research investigations. After multilateral collection and discussion of the substance, we have reached the following conclusions: - The importance of social media sites is that charitable campaigns across them are effective. - The role of social media sites in the success of the Association's activities and programmes is coupled with the promotion of charitable activities. - The Society cannot dispense with social media sites where the Society is keen to register its permanent presence. Key words: Social Media Sites, Charities, Al-Baraka Charity Association, Laghouat.